Pengaruh Academic Resilience terhadap Academic Burnout pada Mahasiswa Program Studi Psikologi Islam UIN Antasari Banjarmasin Pasca Pandemi - Jinan, Khalda Farah (Sultan Idris Journal of Psychology and Education, 2023)
This study aims to determine the effect of academic resilience on post-pandemic academic burnout in students of the Islamic Psychology Study Program at UIN Antasari Banjarmasin. Data collection is done using a questionnaire in the form of a Likert scale. The questionnaire contains Schaufeli and Salova scale items adapted from the Maslach Burnout Inventory-Student Survey (MBI-SSS) scale, which has been translated by Isma Damayanti, S. Psi. This scale uses 15 statement items, as well as a scale from Cassidy, whose name is the Academic Resilience Scale (ARS-30), with a total of 30 statement items. In the simple regression test results, it was found that the correlation values of R and R Square were 0.581 and 0.338, meaning that the effect of academic resilience on academic burnout was 33.8%. Therefore, based on the significance value of the direct regression test, it is possible to draw the conclusion that Ha is accepted, which indicates that there is a positive influence as well as a substantial influence on academic resilience and academic burnout among Islamic Psychology Study Program students at UIN Antasari, with the level of relationship strength in the strong category.